2015
DOI: 10.1159/000381626
|View full text |Cite
|
Sign up to set email alerts
|

Passive Immunization against Congenital Cytomegalovirus Infection: Current State of Knowledge

Abstract: Primary infection with the human cytomegalovirus (CMV) occurs in 1-4% of pregnancies. The rates of maternal-fetal CMV transmissions are around 25, 36, 41, and 66%, for infections occurring in the peri-conceptional weeks, first, second, and third trimester of pregnancy, respectively. On the other hand, the severity of fetal organ damage and dysfunction diminishes with increasing gestational age. Congenitally CMV-infected newborns may have neurosensory impairments like mental retardation, cerebral palsy, epileps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 81 publications
1
18
0
Order By: Relevance
“…This result agrees with the report that blood transfusion was shown to be a risk factor for transmission of CMV infection (Matos et al, 2010). This is true because CMV testing is not part of laboratory screening in blood transfusion services, coupled with the high IgM seropositivity in African societies, recipients are either endangered with contracting CMV infections or acquire passive immunity from IgG seropositive donors (Juckstock et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…This result agrees with the report that blood transfusion was shown to be a risk factor for transmission of CMV infection (Matos et al, 2010). This is true because CMV testing is not part of laboratory screening in blood transfusion services, coupled with the high IgM seropositivity in African societies, recipients are either endangered with contracting CMV infections or acquire passive immunity from IgG seropositive donors (Juckstock et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Modest fetal neurodevelopmental outcomes with the model we have described in this current report may provide an opportunity to further evaluate factors which foster severe fetal developmental impact, such as co-infection or previous exposure to other pathogens, and support the development of strategies to prevent maternal-fetal transmission and reduce fetal virus burden. Further information on the ontogeny of fetal infection and distribution of virus in the fetus during gestation using relevant animal models will be important to establish before consideration of interventional strategies, such as maternal or fetal passive immunization [51] in pregnant women presenting with symptoms of ZIKV infection.…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, Nigro and Adler [6] reported both antiviral and immunomodulatory activities, which are crucial in regulating the innate and adaptive immune responses in the interplay between infection control and immunopathological processes. Studies on murine brains suggested that antibody treatment could mitigate inflammatory tissue damage and CMV replication [7, 8]. Furthermore, a study performed on a small group of human placentas showed that HIG can suppress CMV replication and induce compensatory mechanisms to prevent placental hypoxia, thus improving fetal outcome [9].…”
Section: Introductionmentioning
confidence: 99%